2021
DOI: 10.1111/tmi.13689
|View full text |Cite
|
Sign up to set email alerts
|

Ownership and use of insecticide‐treated nets under Ghana’s National Malaria Control Program: What are the correlates?

Abstract: Malaria remains a significant health threat in Ghana, and by extension, many sub-Saharan African countries. It is caused by the protozoan parasite Plasmodium, which is transmitted by female Anopheles mosquitoes, which usually bite between sunset and sunrise [1]. Africa accounted for 93% of the 228 million malaria cases in 2018 [2]. Globally, malaria caused 405,000 estimated deaths in 2018, with Africa accounting for 94% of the total deaths. Children below 5 years are the most vulnerable group affected by malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Only one systematic review has investigated the prevalence of P. vivax malaria in Duffy-negative individuals [46][47][48][49][50][51][52][53]. This review revealed that 100% of Duffy-negative subjects had reported cases of P. vivax malaria in 11 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Only one systematic review has investigated the prevalence of P. vivax malaria in Duffy-negative individuals [46][47][48][49][50][51][52][53]. This review revealed that 100% of Duffy-negative subjects had reported cases of P. vivax malaria in 11 studies.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, women (pregnant and non-pregnant) are most likely to be advised to use TBNs [ 27 ]. This notwithstanding, although most women (pregnant and non-pregnant) (around eighty-five percent (85%)) have TBNs [ 27 ], a greater proportion do not use them [ 28 , 29 ]. Several factors, including pregnancy status, health status (i.e anaemia level) etc., have been found to influence the usage of TBNs among women in Ghana [ 20 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among those who have access to ITNs, only 43% of the household population use them and the differences between access to and use of ITNs is larger in urban population (59% versus 28%) than in rural households (74% versus 57%) ( Ghana Statistical Service (GSS), and and ICF, 2020 ). Skin irritation, individuals who perceive themselves as not likely to be beaten by mosquitoes or get malaria ( Mensah and Anto, 2020 ), poor wealth index ( Bawuah and Ampaw, 2021 ; Kanmiki et al, 2019 ), individual age ( Konlan et al, 2019 ) among others are some factors that hamper mosquito bed net usage in Ghana.…”
Section: Introductionmentioning
confidence: 99%